(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
This paper constitutes the first voucher record of the cannel scabbardfish, Evoxymetopon taeniatus (Pisces: Trichiuridae) captured at Isla Aguja, Magdalena, Colombia on March 30 of 2009. The specimen was caught with a gillnet at a depth of 18 m.